2020
DOI: 10.1088/1755-1315/484/1/012101
|View full text |Cite
|
Sign up to set email alerts
|

Natural enemy population of corn main pests in Maros experimental station at various stages of plant growth

Abstract: The study of natural enemy population density among the main predator species of corn plants was conducted in Maros Experimental Station (ES), Research Institute for Cereal Crops in 2018. The research uses direct patrol techniques, conducted by making direct observations in the field to record the presence of natural enemies. The natural enemies are observed by referring to Shepard et al. (1987) about insects which are beneficial for biological control of food crop pests. Identification of the presence of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Spiders have a sucking mouth type where the fangs of the Oxyopes lineatipes spider can paralyze their prey. After that, the liquid in the prey's body, can kill 2-3 moths every day, so its presence is significant in preventing the increase in the population of a new generation of insect pests (Saenong et al, 2020). In the research carried out, spiders found that when chili entered the generative phase, these spiders were active during the day and became predators of the moth plant pest (Spodoptera sp.…”
Section: Fire Ant (Solenopsis Invicta)mentioning
confidence: 99%
See 1 more Smart Citation
“…Spiders have a sucking mouth type where the fangs of the Oxyopes lineatipes spider can paralyze their prey. After that, the liquid in the prey's body, can kill 2-3 moths every day, so its presence is significant in preventing the increase in the population of a new generation of insect pests (Saenong et al, 2020). In the research carried out, spiders found that when chili entered the generative phase, these spiders were active during the day and became predators of the moth plant pest (Spodoptera sp.…”
Section: Fire Ant (Solenopsis Invicta)mentioning
confidence: 99%
“…Jumping spiders were found in the morning and afternoon. An adult spider can prey on 2-8 prey per day (Saenong et al, 2020). In the research area, the jumping spider is a predator of the seed fly pest (Aterigona sp.…”
Section: Fire Ant (Solenopsis Invicta)mentioning
confidence: 99%